BIOPORE INFILTRATION HOLES WITH ORGANIC FERTILIZER FOR ENHANCING SOIL NUTRIENTS AND COFFEE PRODUCTION IN ACIDIC CLAY SOILS - Jauhary, Muhammad Rifqi Al; Soemarno; Munir, Mochammad (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2025)
The decreasing land area for coffee cultivation in Indonesia has led to a reduction in coffee production. The availability of land with potential for coffee plantation is also decreasing. As a consequence, coffee is cultivated on less fertile lands, such as lands dominated by clay fraction. This land generally has a low pH so that the nutrient content is more absorbed in Al and Fe which react in an acidic environment. Furthermore, heavy texture of soil also inhibits root growth, making it difficult for plants to absorb nutrients. In this study, biopore infiltration holes were used as a solution to improve acidic soil with a dominant clay fraction. The research was conducted at Agrotechnopark Jatikerto, Malang Regency and the soil analysis was conducted at the Soil Chemistry Laboratory, Faculty of Agriculture, University of Brawijaya during 2020-2022. This research was conducted experimentally with a group randomized design. There were four treatments in this study, namely 1) control/no biopore, 2) 30 cm empty biopore, 3) 30 cm biopore + 2.12 kg compost fertilizer, and 4) 30 cm biopore + 1.05 kg goat manure fertilizer. The results showed that biopore infiltration holes added with compost or goat manure fertilizer were able to increase pH, soil organic C, CEC, BS, and total N-P-K nutrients. Furthermore, the increase in organic C and total N-P-K nutrients in the study area was also directly proportional to the increase in chlorophyll content and coffee production. The increase in chlorophyll content and coffee production is a result of the increase in chlorophyll content and coffee yield.